Micro-nano composite structure for enhancing boiling heat transfer of low-temperature fluid, processing method and application
Through femtosecond laser processing technology, the micro-nano composite lattice structure surface is prepared in the boiling heat transfer of low-temperature fluid, which solves the problem of heat transfer deterioration caused by the formation of gas film during the boiling process of low-temperature fluid, and achieves efficient boiling heat transfer performance improvement of low-temperature fluid.
Patent Information
- Application Number
- CN202510057617.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-25
AI Technical Summary
During the boiling process, low-temperature fluids are prone to form gas films, causing local drying, deteriorating heat transfer, and difficult to increase the boiling heat flow density.
The surface of the micro-nano composite lattice structure is prepared by femtosecond laser processing technology. By forming a lattice structure with a similar vertical and horizontal spacing on the substrate surface of the high-thermal conductivity material, combined with the adhesion of nanoparticle oxide powder, a peak-to-valley micro-nano composite structure is formed.
It significantly improves the boiling heat transfer performance of low-temperature fluids, improves the critical heat flow density, delays the occurrence of film boiling, and ensures efficient heat transfer under low-temperature conditions.
Smart Images

Figure CN119873736A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of micro-nano manufacturing and heat transfer application, and specifically relates to a micro-nano composite structure, a processing method and an application for enhancing boiling heat transfer of a low-temperature fluid. Background Art
[0002] Cryogenic fluids have unique physical properties such as low boiling point, low viscosity, and low surface tension, and are widely used in scientific research and industrial production. In the field of superconductivity research, liquid nitrogen pool boiling is often used to quickly reduce the temperature of the material and put it into a superconducting state. In the field of aerospace, cryogenic fluids such as liquid hydrogen, liquid oxygen, and liquid methane are often used as propellants to provide powerful power for rocket engines. The cooling of their cryogenic storage tanks often uses boiling heat transfer of other cryogenic fluids to reduce the loss of liquid hydrogen and liquid oxygen. In the biomedical field, cryogenic fluids can be used to preserve cells and biological tissues for a long time, so that they still maintain their biological activity after thawing. In addition, in the field of metallurgy, for the processing of some special metals, such as titanium alloys with low thermal conductivity, special processes such as cryogenic cooling are required to increase the brittleness of the material, thereby improving its processing performance. Therefore, strengthening the heat exchange of cryogenic fluids is of great significance to aerospace, medical health, superconducting technology, and industrial processing.
[0003] Micro-nano structures are often used to enhance the boiling heat transfer of room temperature fluids (such as water, ethanol, and fluorinated liquids). Among them, nanostructures can effectively enhance surface wettability and capillary forces, and increase the nucleation and detachment frequency of bubbles in the early stage of boiling. For example, the TiO2 nanowire coating prepared on the copper surface by electron beam evaporation technology can increase its critical heat flux (CHF) to 186%; at the same time, microstructures mainly enhance boiling heat transfer by increasing the density of nucleation points. The Al2O3 porous micro-coated copper surface constructed by single-step electrodeposition can increase CHF to 172.5%; in addition, micro-nano composite surfaces can achieve functional synergy on a spatial scale, thereby enhancing the boiling heat transfer process at multiple scales. For example, the Si microcavity-Si nanowire composite surface constructed by photolithography combined with deep reactive ion etching and metal-assisted etching can increase CHF to 270%.
[0004] Cryogenic fluids (such as liquid nitrogen, liquid oxygen, and liquid helium) have unique physical properties that are different from room-temperature fluids (such as water and oil) and refrigerants (such as R12 and R134a). Their microscopic boiling processes are different from those of room-temperature fluids: (1) Cryogenic fluids have low latent heat of vaporization and are prone to forming gas films, which can cause local drying and deteriorate heat transfer; (2) Cryogenic fluids have low surface tension and low viscosity, and have good wettability, making them easier to spread on solid surfaces; (3) Cryogenic fluids will greatly reduce the boiling surface temperature, causing changes in the surface thermal properties and thus affecting boiling.
[0005] Therefore, the boiling mechanism of low-temperature fluids is different from that of normal-temperature fluids, and there is an urgent need to develop structural surfaces to enhance the boiling heat transfer of low-temperature working fluids. Summary of the invention
[0006] In order to solve the above technical problems, the present invention adopts femtosecond laser processing technology to prepare the surface of micro-nano composite lattice structure to enhance the boiling heat transfer performance of low-temperature fluid. The process has the following advantages: 1. It can achieve high precision of micron-level lattice, and because the pulse time of femtosecond laser is extremely short, the heat-affected zone generated during the processing is extremely small, which can avoid thermal damage and deformation of the material; 2. During femtosecond laser processing, part of the material evaporates, oxidizes and condenses quickly, and then a layer of nanoparticles is covered on the micron lattice structure, thereby forming a micro-nano composite structure; 3. As a non-contact processing method, femtosecond laser will not apply mechanical stress to the material, avoiding damage and deformation of the material caused by mechanical action; 4. It has a wide range of material applicability and can process a variety of materials including metals, ceramics, glass, and plastics; 5. The processing speed is fast, which can significantly shorten the production cycle and reduce manufacturing costs, and no chemical reagents are required, further reducing environmental pollution and energy consumption.
[0007] The present invention provides the following technical solutions: a micro-nano composite structure for enhancing boiling heat transfer of low-temperature fluid, wherein the micro-nano composite structure uses a solid material with high thermal conductivity as a substrate and is processed on the surface of the substrate using a femtosecond laser;
[0008] The micro-nano composite structure is a lattice structure with similar vertical and horizontal spacing formed on the surface of the substrate. The lattice structure forms a peak-valley structure from the surface to the inside along the surface of the substrate. The valley of the peak-valley structure is circular, and the diameter of the valley ablation point is not less than the spacing between adjacent points.
[0009] The peak-and-valley structure is attached with nanoparticle oxide powder formed on the substrate surface during laser ablation.
[0010] Preferably, the material of the substrate includes metal and non-metal solids; metal materials include silver, gold, copper, iron, aluminum, nickel, lead, zinc, titanium, chromium and their alloys, and non-metal materials include silicon, silicon carbide, silicon dioxide, polytetrafluoroethylene, rubber, ceramics, carbon, and diamond; in particular, when the material of the substrate is metallic silver, the nanoparticle oxide powder is Ag2O particles.
[0011] Preferably, the micro-nano composite structure includes: a microstructure and a nanostructure;
[0012] The microstructure is a micron-scale protrusion or depression; the microstructure is used to increase the actual area of the heat exchange surface, increase the density of bubble nucleation sites, thereby reducing the superheat required for bubble nucleation, improving the heat transfer coefficient and critical heat flux density of the substrate, and improving the heat transfer efficiency of nucleate boiling;
[0013] The nanostructure is a nanoparticle oxide powder formed during the laser ablation process of the substrate and attached to the microstructure; the nanostructure is used to enhance the capillary force of the structure surface on the contacting liquid, induce capillary wicking, strengthen the solid-liquid contact and promote the rewetting of the structure surface by the liquid, thereby increasing the boiling critical heat flux density.
[0014] Preferably, the vertical and horizontal spacing of the lattice structure formed on the substrate surface ranges from 10 μm to 100 μm; the diameter of the ablation point ranges from 10 μm to 100 μm, and the depth ranges from 10 μm to 100 μm; and the material thickness of the substrate ranges from 30 μm to 5 mm.
[0015] The present invention also discloses a processing method for a micro-nano composite structure for enhancing boiling heat exchange of a low-temperature fluid. The processing method is used to process the above-mentioned micro-nano composite structure. The processing method is:
[0016] The substrate sheet is fixed on the processing station of the three-dimensional precision translation stage; by adjusting the number of pulses, laser power and the position of the three-dimensional precision translation stage, the laser is used to process a dot matrix structure with similar horizontal and vertical spacing on the substrate sheet, wherein the laser power affects the diameter of the laser ablation point, and the number of pulses affects the depth of the ablation point, so that the diameter of the ablation point is not less than the spacing between adjacent points, thereby forming a peak-valley structure on the surface of the substrate sheet.
[0017] The present invention also discloses an application of a micro-nano composite structure for enhancing boiling heat transfer of a cryogenic fluid. The application adopts the above-mentioned micro-nano composite structure and uses the micro-nano composite structure for heat transfer of the cryogenic fluid during boiling.
[0018] Preferably, the cryogenic fluid includes: liquid nitrogen, liquid helium, liquid neon, liquid argon, liquid krypton, liquid hydrogen, liquid oxygen, liquid methane, and liquid carbon dioxide.
[0019] The beneficial effects of the present invention are:
[0020] 1. The principle of the present invention is simple and easy to implement, and the preparation and use process is concise.
[0021] 2. The material of the present invention has excellent thermal conductivity and can maintain good heat transfer efficiency even under low temperature conditions.
[0022] 3. The femtosecond laser processing method of the present invention has an extremely short pulse time, and the heat-affected zone generated during the processing is extremely small, thus avoiding thermal damage and deformation of the structure surface.
[0023] 4. The femtosecond laser processing method of the present invention has a fast processing speed, can significantly shorten the production cycle and reduce manufacturing costs.
[0024] 5. The femtosecond laser processing method of the present invention can prepare micron structures by moving the three-dimensional processing console, prepare nanostructures by regulating the energy of the femtosecond laser, and finally form a peak-and-valley micro-nanostructure composite surface in one go.
[0025] 6. The femtosecond laser processing method of the present invention is non-contact, has strong adaptability to the environment, and does not cause damage and deformation due to mechanical processing. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a micro-nano composite structure diagram observed under a scanning electron microscope of the micro-nano composite structure, processing method and application for enhancing boiling heat transfer of low-temperature fluids of the present invention;
[0027] Figure 2 It is a schematic diagram of an experimental device for performing pool boiling of liquid nitrogen on the surface of a micro-nano composite structure of the present invention;
[0028] Figure 3 It is a curve diagram showing the temperature variation over time of the surface of the micro-nano composite structure during the liquid nitrogen pool boiling process of the present invention. DETAILED DESCRIPTION
[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the relevant technologies in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] like Figures 1 to 3 As shown, this embodiment aims to solve the problem that low-temperature fluid has low surface tension, low viscosity, and low latent heat, and is prone to air film formation during boiling heat transfer, resulting in local drying, thereby deteriorating heat transfer and making it difficult to increase boiling heat flux density. A micro-nano composite structure processed by femtosecond laser is proposed, which greatly improves the critical heat flux density of boiling heat transfer of low-temperature fluid.
[0031] In order to achieve the above objectives, the following scheme is adopted:
[0032] This embodiment uses liquid nitrogen as a representative of low-temperature fluid to design a boiling heat transfer enhancement scheme. Thin sheet solid materials (such as silver sheets, silicon sheets) are used as substrates, and femtosecond lasers are used to process micro-nano composite structures on their surfaces.
[0033] A silver sheet with a thickness of 100 μm was used as the processing object, and the silver sheet was fixed on the processing station of the three-dimensional precision translation stage. By adjusting the number of pulses, laser power and the position of the three-dimensional precision translation stage, the laser was used to process a dot structure with a horizontal and vertical spacing of 50 μm on the silver sheet. Among them, the laser power affects the diameter of the laser ablation point, and the number of pulses affects the depth of the ablation point. When the diameter of the ablation point is equal to the spacing between adjacent points, the following will be formed. Figure 1 The peak-and-valley structure shown;
[0034] Specific parameters in this embodiment are: laser wavelength of 1030nm, repetition rate of 2kHz, pulse width of 240fs, number of pulses of 1800, laser power of 2W, and peak-valley structures of different sizes can be obtained by adjusting the processing point spacing and laser parameters;
[0035] The peak-valley structure on the sample surface is at the micron level, which can significantly increase the effective heat transfer area and bubble nucleation site density during the boiling process, reduce the starting point temperature of nucleate boiling and improve the boiling heat transfer efficiency. The silver oxide powder formed on the surface of the silver sheet during laser ablation will adhere to the peak-valley structure as nanoparticles, improve the wettability of the liquid on the surface of the structure during boiling, promote the detachment of bubbles, increase the critical heat flux density and inhibit film boiling. Therefore, this micro-nano composite structure can enhance the boiling heat transfer performance of low-temperature fluids.
[0036] The micro-nano composite structure based on femtosecond laser processing proposed in this embodiment adopts a solid material with relatively large thermal conductivity (silver sheet, silicon wafer) as a substrate, and forms a peak-valley-shaped micro-nano structure composite surface through femtosecond laser processing, wherein the micron structure is regulated by a femtosecond laser mobile three-dimensional processing control console, and the nanostructure is nanoparticles formed during the femtosecond laser processing, which are regulated by the femtosecond laser energy.
[0037] The preferred method of this embodiment uses a solid material represented by silver as the substrate. This material has excellent thermal conductivity and can maintain good heat transfer efficiency even under low temperature conditions. The micro-nano composite structure processed by femtosecond laser avoids thermal damage and deformation, and as a contactless processing, there is no damage and deformation caused by mechanical processing, so that the processed structure is complete and evenly distributed. Through structural design and adjustment of laser processing parameters, different micro-nano structure surfaces can be designed to meet actual application needs. The processed structures can be divided into the following types according to scale:
[0038] (1) Microstructure:
[0039] Microstructure can significantly increase the actual area of heat transfer surface by adding microscopic protrusions or depressions, such as Figure 1. At the same time, the microstructure is conducive to capturing gas in defects, increasing the density of bubble nucleation sites and providing sufficient space for bubble growth and detachment, thereby reducing the superheat required for bubble nucleation, improving its heat transfer coefficient and critical heat flux density, and improving the heat transfer efficiency of nucleate boiling. In addition, the microstructure increases the thickness of the stable steam layer required for film boiling, thereby inhibiting the generation of gas film during boiling and enhancing the boiling heat transfer performance.
[0040] (2) Nanostructure:
[0041] Nanostructures can enhance the capillary force of the structural surface on the contacting liquid, induce capillary wicking phenomenon, strengthen solid-liquid contact and promote the rewetting of the liquid on the structural surface, which is beneficial to inhibit the formation of gas film in the boiling process and increase the bubble detachment frequency in the nucleate boiling process, thereby increasing the critical heat flux density of boiling.
[0042] (3) Micro-nano composite structure:
[0043] In the micro-nano composite structure, the microstructure can promote the nucleation and growth of bubbles. However, under high heat flux conditions, bubbles tend to merge to form a vapor layer that hinders the reflux of the liquid phase. The nanostructure can provide a strong capillary force to promote the detachment of bubbles and accelerate the reflux of the liquid phase. The synergistic effect of the two-scale structures can reduce the resistance between bubble escape and liquid reflux, increase the critical heat flux density, enhance the heat transfer efficiency, and delay the occurrence of film boiling.
[0044] Therefore, in this embodiment, adjacent micrometer-level holes and peak-valley-shaped micro-nano composite structures are processed on the silver sheet by combining femtosecond laser with a three-dimensional processing console. The schematic diagram of the processed structure is shown in the attached figure. Figure 1 Given. Figure 1 As shown, the spacing between the peaks and valleys is 55 μm, the depth is 48 μm, and nanoscale Ag2O particles formed by laser ablation are distributed on the peaks and valleys.
[0045] The temperature variation curve of the surface of the micro-nano composite structure (with a 100 μm silver sheet as the substrate and liquid nitrogen as the working fluid) during pool boiling is shown in the attached figure. Figure 3 The experiment shows that compared with the smooth silver sheet surface, the peak-valley micro-nano composite structure processed by femtosecond laser can shorten the surface cooling time of liquid nitrogen boiling by more than half, and its critical heat flux density can be increased by more than two times. It can be seen that the heat transfer rate and critical heat flux density of the micro-nano composite surface processed by femtosecond laser are greatly improved, so this structure can greatly improve the boiling heat transfer performance of liquid nitrogen.
[0046] The micro-nano composite structure proposed in this embodiment can promote the nucleate boiling of low-temperature fluids, inhibit their film boiling, and thus enhance their boiling heat transfer performance. Taking the case of a micro-nano structure surface prepared by a silver sheet as a solid substrate, a femtosecond laser as a structural processing method, and a peak-and-valley-shaped micro-nano composite structure as a surface structure as an example, the main process of the preparation and use of this structure is described. A pool boiling experiment is carried out using liquid nitrogen as a working fluid to explain the mechanism by which this structure enhances the boiling heat transfer performance of low-temperature fluids. Pool boiling experimental apparatus and method:
[0047] The device has two chambers (liquid nitrogen chamber and freezing chamber) made of polytetrafluoroethylene (PTFE) to prevent potential chemical corrosion and deformation of the device during the freezing process. The boiling surface is prepared by 100μm silver sheet (since silver has high thermal conductivity of 429W / (m·K)), it still maintains good heat transfer performance even at low temperatures). Before pasting the boiling surface between the two chambers, a thin layer of low-temperature sealant is applied to the exposed surfaces of the two chambers to prevent liquid nitrogen from leaking from the liquid nitrogen chamber. The two chambers are then fixed together with plastic bolts. The liquid nitrogen chamber is used to contain liquid nitrogen for boiling heat transfer on the surface of the micro-nano composite structure. T-type thermocouples are pasted in both the liquid nitrogen chamber and the freezing chamber to measure and record the temperature changes on the surface of the structure.
[0048] Liquid nitrogen was used as the working fluid in the experiment, and boiling was performed under standard atmospheric pressure (101.3 kPa). The temperature change at the center of the structure surface measured by a T-type thermocouple was recorded by a data logger at a sampling time interval of 10 ms.
[0049] Experimental data processing:
[0050] The measured temperature data is recorded as the wall temperature T w , then the structural surface superheat is ΔT w =T w -T sat (The saturation temperature of liquid nitrogen is T sat =-196°C).
[0051] Critical heat flux (W / m 2 ) can be obtained by the formula q = mc p [T(t1)-T(t2)] / Δt=ρhc p [T(t1)-T(t2)] / Δt calculation, where m(Kg / m 2 ) is the unit mass of the boiling surface, c p (J / kg·K) is the specific heat capacity of the surface material, [T(t1)-T(t2)](K) is the temperature difference at the center of the structure surface during the time interval Δt(s), ρ(kg / m 3 ) is the density of the surface material and h(m) is the thickness of the boiling surface.
[0052] In summary, the method principle is simple and easy to implement, and the preparation and use process is concise. The structure of the present invention has excellent thermal conductivity and can maintain good heat transfer efficiency even under low temperature conditions. Therefore, the present invention has broad application prospects in the field of enhancing the boiling heat transfer performance of low-temperature fluids.
[0053] It should be emphasized that the above are only preferred embodiments of the present invention and do not limit the present invention in any form. Any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A micro-nano composite structure for enhancing boiling heat transfer of low-temperature fluids, characterized in that: The micro-nano composite structure uses a solid thin sheet material as a substrate and is processed on the surface of the substrate using a femtosecond laser; The micro-nano composite structure is a lattice structure with similar vertical and horizontal spacing formed on the surface of the substrate, the lattice structure is a peak-valley structure from the outside to the inside along the surface of the substrate, the valley mouth of the peak-valley structure is circular, and the diameter of the valley mouth ablation point is not less than the size of the spacing between adjacent points; The peak-valley structure is adhered with nano-particle oxide powder formed on the surface of the substrate during the laser ablation process.
2. The micro-nano composite structure for enhancing boiling heat transfer of low-temperature fluid according to claim 1, characterized in that: The material of the substrate includes metal and non-metal solids; the metal includes silver, gold, copper, iron, aluminum, nickel, lead, zinc, titanium, chromium and alloys thereof, and the non-metal includes silicon, silicon carbide, silicon dioxide, polytetrafluoroethylene, rubber, ceramics, carbon and diamond; when the material of the substrate is metallic silver, the nanoparticle oxide powder is Ag2O particles.
3. The micro-nano composite structure for enhancing boiling heat transfer of low-temperature fluid according to claim 1, characterized in that: The micro-nano composite structure includes: a micron structure and a nano structure; The microstructure is a micron-scale protrusion or depression; the microstructure is used to increase the actual area of the heat exchange surface, increase the density of bubble nucleation sites, thereby reducing the superheat required for bubble nucleation, improving the heat transfer coefficient and critical heat flux density of the substrate, and improving the heat transfer efficiency of nucleate boiling; The nanostructure is a nanoparticle oxide powder formed during the laser ablation of the substrate and attached to the microstructure; the nanostructure is used to enhance the capillary force of the structure surface on the contacting liquid, induce capillary wicking phenomenon, strengthen solid-liquid contact and promote the rewetting of the structure surface by the liquid, thereby increasing the boiling critical heat flux density.
4. The micro-nano composite structure for enhancing boiling heat transfer of low-temperature fluid according to claim 1, characterized in that: The vertical and horizontal spacing of the lattice structure formed on the surface of the substrate ranges from 10 μm to 100 μm; the diameter of the ablation point ranges from 10 μm to 100 μm, and the depth ranges from 10 μm to 100 μm; the material thickness of the substrate ranges from 30 μm to 5 mm.
5. A method for processing a micro-nano composite structure for enhancing boiling heat transfer of low-temperature fluids, characterized in that: The processing method is used to process the micro-nano composite structure described in any one of claims 1 to 4. The processing method includes fixing the substrate sheet on the processing station of the three-dimensional precision translation stage, and adjusting the laser power, the number of pulses and the position of the three-dimensional precision translation stage so that the laser processes a lattice structure on the substrate sheet with an ablation point diameter close to the adjacent point spacing, wherein the laser power is adjusted to change the laser ablation point diameter, and the pulse number is adjusted to change the ablation point depth, so that the ablation point diameter is close to but not less than the adjacent point spacing, thereby forming a peak-valley structure on the surface of the substrate sheet.
6. An application of a micro-nano composite structure for enhancing boiling heat transfer of low-temperature fluids, characterized in that: The application adopts the micro-nano composite structure described in any one of claims 1 to 4, and the application uses the micro-nano composite structure for heat transfer during boiling of low-temperature fluid.
7. The use of a micro-nano composite structure for enhancing boiling heat transfer of low-temperature fluid according to claim 6, characterized in that: The cryogenic fluid includes: liquid nitrogen, liquid helium, liquid neon, liquid argon, liquid krypton, liquid hydrogen, liquid oxygen, liquid methane, and liquid carbon dioxide.